2022
DOI: 10.3390/land11071097
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the Economic Development from Resource Consumption: Implications and Challenges in Assessing the Evolution of Forest Area in Romania

Abstract: The paper proposes an insight into the relation existing between economic development and resource consumption and the associated implications and challenges for forested areas in Romania. In accordance with this purpose, the methods used are both qualitative and quantitative by using a relevant literature review, including international and national reports. In the 1950s and 1960s, Simon Kuznets introduced to modern economic theory the idea that there are certain market forces directly correlated with economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Rădulescu et al [4] found that there exists an inverse-U-shaped correlation between GDP and Romania's forested areas. The study by Murshed et al [14] examined the EKC hypothesis for Bangladesh.…”
Section: Economic Growth and Deforestationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rădulescu et al [4] found that there exists an inverse-U-shaped correlation between GDP and Romania's forested areas. The study by Murshed et al [14] examined the EKC hypothesis for Bangladesh.…”
Section: Economic Growth and Deforestationmentioning
confidence: 99%
“…The effort to achieve the EU's goal of decarbonizing its economy by 2050 includes the promotion of sustainable bioenergy as a substitute for fossil fuels. Hence, there is a need for strategies focused on sustainable forest management and the preservation of biodiverse areas, aimed at utilizing biomass for the generation of electricity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the discourse by Burlacu et al (2018) on e-commerce and global food resources implies that the proposed Information System for the Romanian Agricultural and Food Products Market (SIPPAA) information platform could integrate e-commerce into the short local and proximity value chains for micro-businesses. Lastly, the discussion by Rădulescu et al (2022b) on the implications and challenges in assessing Romania's forest area evolution suggests that the research could underscore the role of sustainable agri-food technologies in decoupling economic development from resource consumption. In summary, the specialized literature highlights multiple challenges related to food security, renewable sources, rural migration, and sustainable development.…”
Section: The State Of Knowledge In the Field Specialty Literaturementioning
confidence: 99%
“…Their research underscores the urgency of developing sustainable strategies within the mountain agro-food sector, emphasizing the imperative of ensuring economic and food security on a global scale. Rădulescu et al (2022) direct our attention to the vital concept of decoupling economic development from resource consumption. This notion aligns seamlessly with our exploration of sustainable growth in mountainous regions, where innovative approaches must strike a delicate balance between fostering economic progress and minimizing resource depletion.…”
Section: Specialized Literature and Knowledge In The Fieldmentioning
confidence: 99%